1994
DOI: 10.1542/peds.93.6.a36
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Overdose as a Suicidal Gesture: A Survey of Adolescents' Knowledge of Its Potential for Toxicity

Abstract: Acetaminophen is a popular nonprescription analgesic that is often taken in overdose by adolescents during suicidal gestures. The authors hypothesized that most adolescents are naive about the toxic and lethal potential of acetaminophen in overdose. A one-page, 12-item questionnaire was administered to 169 high school students to evaluate their perceptions and knowledge in this area. Whereas only 22% of the sample underestimated the dose of acetaminophen necessary to cause harm, 40.5% underestimated the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The increase in poisoning is noteworthy as the long-term consequences of cardiac and hepatic toxicity may not be appreciated by youths. 28 Besides confirming patients with schizophrenia and mood disorders having increased risk of repeated selfinflicted injuries as reported in other studies, 16,20,29 our findings also showed a higher proportion of children with previous self-harm having multiple psychiatric diagnoses compared with children without a history of self-inflicted injury. A strong doseeresponse relationship between the number of mental health disorders and risk of subsequent suicide attempt had been demonstrated.…”
Section: Discussionsupporting
confidence: 90%
“…The increase in poisoning is noteworthy as the long-term consequences of cardiac and hepatic toxicity may not be appreciated by youths. 28 Besides confirming patients with schizophrenia and mood disorders having increased risk of repeated selfinflicted injuries as reported in other studies, 16,20,29 our findings also showed a higher proportion of children with previous self-harm having multiple psychiatric diagnoses compared with children without a history of self-inflicted injury. A strong doseeresponse relationship between the number of mental health disorders and risk of subsequent suicide attempt had been demonstrated.…”
Section: Discussionsupporting
confidence: 90%